Outflow and plasma acceleration in Titan's induced magnetotail: Evidence of magnetic tension forces. Issue 12 (19th December 2014) - Romanelli, N.; Modolo, R.; Dubinin, E.; Berthelier, J.‐J.; Bertucci, C.; Wahlund, J. E.; Leblanc, F.; Canu, P.; Edberg, N. J. T.; Waite, H.; Kurth, W. S.; Gurnett, D.; et al.
Abstract Cassini plasma wave and particle observations are combined with magnetometer measurements to study Titan's induced magnetic tail. In this study, we report and analyze the plasma acceleration in Titan's induced magnetotail observed in flybys T17, T19, and T40. Radio and Plasma Wave Science observations show regions of cold plasma with electron densities between 0.1 and a few tens of electrons per cubic centimeter. The Cassini Plasma Spectrometer (CAPS)‐ion mass spectrometer (IMS) measurements suggest that ionospheric plasma in this region is composed of ions with masses ranging from 15 to 17 amu and from 28 to 31 amu. From these measurements, we determine the bulk velocity of the plasma and the Alfvén velocity in Titan's tail region. Finally, a Walén test of such measurements suggest that the progressive acceleration of the ionospheric plasma shown by CAPS can be interpreted in terms of magnetic tension forces.